Design of rectangle microstrip patch array antenna for UWB vehicular short range radar application / Nadiy Zaiaami and Idnin Pasya - Zaiaami, Nadiy; Pasya, Idnin (UiTM Press, 2014)
Objective of this paper is to study the design of UWB antenna for short range vehicular application within 20 to 30 GHz frequency range. Initially, a study was conducted on RF requirements for short range vehicular radars, taking into considerations the positions of transmitting and receiving antennas, transmission distance, and antenna beam requirements. For this purpose, numerical calculations were carried out to determine the conditions of main lobe beamwidth to avoid destructive reflections from the ground. Based on these calculations, a microstrip patch array antenna was designed and analyzed using 3D-EM simulations. The parameters that were analyzed include the radiation pattern, side lobe angle return loss and antenna gain. Observation on the controlling parameters of the array antenna was conducted to investigate their effect on radiation pattern and side lobes. And efficiency of the design with different dimension of the design include size patch, length and width of transformer, length and width of feedline, and length and width of substrate.